Liquid film thickness behaviour within a large diameter vertical 180° return bend - Adbulkadir, M.; Azzi, A.; Zhao, D.; Azzopardi, Barry J. (Elsevier, 2014)
Experimental results of liquid film thickness distribution of an air–water mixture flowing through a vertical 180° return bend are reported. Measurements of liquid film thickness were achieved using flush mounted pin and parallel wire probes. The bend has a diameter of 127 mm and a curvature ratio (R/D) of 3. The superficial velocities of air ranged from 3.5 to 16.1 m/s and those for water from 0.02 to 0.2 m/s. At these superficial velocity ranges, the flow pattern investigated in this work focused on churn and annular flows. It was found that at liquid and gas superficial velocities of 0.02 m/s and 6.2 m/s, respectively, the averaged liquid film thickness peak at 90°. At gas superficial velocity of 16.1 m/s, the relationship between them is linear due to the shear forces overcoming gravity. Additionally, it was found that deposition of entrained droplets keeps the liquid film on the outside of the bend. The results of polar plots of average liquid film thickness in the bend showed that the distribution of the liquid film is not symmetrical with thicker films on the inside of the bend due to the action of gravity. Experimental results on average liquid film thickness showed good agreement with the simulation data reported in the literature.